You can swim but you can't hide: the global status and conservation of oceanic pelagic sharks and rays - Dulvy, Nicholas K; Baum, Julia K; Clarke, Shelley; Compagno, Leonard J.V; Cortés, Enric; Domingo, Andrés; Fordham, Sonja; Fowler, Sarah; Francis, Malcolm P; Gibson, Claudine; Martínez, Jimmy; Musick, John A; et al. (Aquatic conservation, 2008)
1.Fishing spans all oceans and the impact on ocean predators such as sharks and rays is largely unknown. A lack of data and complicated jurisdictional issues present particular challenges for assessing and conserving high seas biodiversity. It is clear, however, that pelagic sharks and rays of the open ocean are subject to high and often unrestricted levels of mortality from bycatch and targeted fisheries for their meat and valuable fins.2.These species exhibit a wide range of life-history characteristics, but many have relatively low productivity and consequently relatively high intrinsic vulnerability to over-exploitation. The IUCN -- World Conservation Union Red List criteria were used to assess the global status of 21 oceanic pelagic shark and ray species.3.Three-quarters (16) of these species are classified as Threatened or Near Threatened. Eleven species are globally threatened with higher risk of extinction: the giant devilray is Endangered, ten sharks are Vulnerable and a further five species are Near Threatened. Threat status depends on the interaction between the demographic resilience of the species and intensity of fisheries exploitation.4.4. Most threatened species, like the shortfin mako shark, have low population increase rates and suffer high fishing mortality throughout their range. Species with a lower risk of extinction have either fast, resilient life histories (e.g. pelagic stingray) or are species with slow, less resilient life histories but subject to fisheries management (e.g. salmon shark).5.5. Recommendations, including implementing and enforcing finning bans and catch limits, are made to guide effective conservation and management of these sharks and rays. Copyright © 2008 John Wiley & Sons, Ltd.